The Implementation of Entrepreneurship Education through Mini Cinema Project at Elementary School - Enny Hidajati; Kurnia Saputri; Sisca Meidina Saputri; Rosmiati Rosmiati (AL-ISHLAH: Jurnal Pendidikan, 2024)
The school can carry out entrepreneurship education by applying it in real terms in the school curriculum content. At Sekolah Dasar (SD) Alam Palembang, the entrepreneurial spirit is one of the main character goals that must be realized. In addition, students have noble character, leadership, and logical thinking. Therefore, at Palembang Elementary School, entrepreneurship is taught through several programs, one of which is a mini cinema project. The research aims to find the implementation of entrepreneurship education through a mini cinema project at SD Alam Palembang. In this study used a qualitative approach with descriptive methods. Data collection techniques using interview techniques, observation, and documentation. Research sources consist of primary and secondary data sources. Primary data is sourced from interviews and observation results. Secondary data to support primary data is documentation relating to the implementation of the mini cinema project. The results of this study indicate that there are six important characteristics in entrepreneurship education. Those characters are independent, creative, hard-working, action-oriented, daring to take risks, and leadership, which can be taught through this mini cinema project. These six entrepreneurial characteristics can be taught directly through a successful mini-cinema project.